2020
DOI: 10.1021/acs.inorgchem.0c01979
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Mediated Spin-State Changes in a Cobalt-Dipyrrin-Bisphenol Complex

Abstract: The influence of a redox-active ligand on spin-changing events induced by the coordination of exogenous donors is investigated within the cobalt complex [Co II (DPP· 2– )] , bearing a redox-active DPP 2– ligand (DPP = dipyrrin-bis( o , p -di- tert -butylphenolato) with a pentafluorophenyl moiety on the meso -positio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Calculations were carried out without inclusion of the solvent (relative permittivity ϵ r of 1), and also with inclusion of a solvent with a relative permittivity ϵ r of 37.5 (close to the value of CH 3 CN), using the conductor‐like screening model (COSMO). Of course, it would be desirable to treat such open‐shell molecules (e. g. cobalt complexes[ 30 , 62 ]) with multireference methods (such as CASSCF). However, multireference calculations are not simple for molecules of that size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculations were carried out without inclusion of the solvent (relative permittivity ϵ r of 1), and also with inclusion of a solvent with a relative permittivity ϵ r of 37.5 (close to the value of CH 3 CN), using the conductor‐like screening model (COSMO). Of course, it would be desirable to treat such open‐shell molecules (e. g. cobalt complexes[ 30 , 62 ]) with multireference methods (such as CASSCF). However, multireference calculations are not simple for molecules of that size.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, dinuclear cobalt complexes with bridging tetraoxolene ligands were the first compounds showing redox‐induced intramolecular electron transfer (RIET), leading to the reduction of the metal atom upon overall oxidation of the complex [27–29] . Recently, it has been shown that the additional coordination of a ligand could trigger spin‐flip or metal‐to ligand single‐electron transfer in cobalt complexes with a dipyrrin‐biphenol ligand [30] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvation of this complex in the weak sp 3 -hybrid donor THF quantitatively affords the octahedral complex [Co II (DPP •2– )(THF) 2 ], which has a triplet spin and again a low-spin cobalt(II) center and ligand-centered radical ( Figure 1 ). 112 The ligand-centered α-spin electron mainly resides in the strongly correlated antibonding combinations of the d yz orbital with the ligand pyrrole π-framework (d yz – Pyr L π ) and the complete ligand π-system (L π –d yz ). The latter is more delocalized over the ligand and bears the major amount of spin density to prevent electron–electron repulsion and thereby enhance radical stabilization.…”
Section: Changing Spin Statesmentioning
confidence: 99%
“…Axial coordination of the stronger donors (L) pyridine (σ-donor, weak π-acceptor), t BuNH 2 , or AdNH 2 (σ-donors, Ad = 1-adamantyl) affords the octahedral complexes [Co III (DPP 3– )(L) 2 ], which all reside in the closed-shell singlet state ( Figure 1 ). 112 The major destabilization of the cobalt-centered d z 2 orbital due to coordination of these strong donors raises the energy of this orbital to such an extent that intramolecular metal-to-ligand single-electron transfer occurs. Consequently, cobalt adopts a low-spin +III oxidation state, and the ligand is reduced to the closed-shell trianionic state.…”
Section: Changing Spin Statesmentioning
confidence: 99%